"I Wasn't Expecting It": High School Experiences and Navigating Belonging in the Transition to College. Issue 1 (February 2022) - Offidani-Bertrand, Carly; Velez, Gabriel; Benz, Claudia; Keels, Micere
For emerging adults transitioning to college, normative social and contextual shifts present challenges that are largely a productive aspect of development. But not all students have the same experiences, nor do all students manage similar experiences in similar ways. Black and Latinx emerging adults transitioning to Historically White Institutions must adjust not only to college life but also to feeling different and, sometimes, isolated. There is a dearth of qualitative work examining how students of color make meaning of their racial-ethnic experiences on campus. Our article draws on a mixed-methods study of Black and Latinx emerging adults' transition to college to investigate how high school racial-ethnic contexts shape students' interpretations of experiences of difference on college campuses. There was substantial variation in how Black and Latinx students interpreted experiences of difference on campus and coped with their feelings of otherness, and this variation was predicted by racial-ethnic high school context.